The Media Barometer 2015 - Nordicom - Nordic Information Centre for Media and Communication Research, University of Gothenburg (University of Gothenburg, 2017)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 2015
Keywords: mass media; massmedia; mass media exposure; massmediaexponering; information and communications technology; informations- och kommunikationsteknologi; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; listening to music; musiklyssnande; television; television; radio; radio; cinema attendance; biobesök; book use; bokanvändning; local broadcasting; lokalsändningar; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; cable television; kabel-tv; television advertising; tv-reklam; television news; tv-nyheter; television programmes; tv-program; local press; lokalpress; advertising; reklam; press advertising; tidningsreklam; television viewing; tv-tittande; internet; internet; internet access; internetåtkomst; electronic mail; elektronisk post; audio and video equipment; ljud- och videoutrustning; teletext; text-tv; mobile communication; mobilkommunikation; access to information and communications technology; tillgång till informations- och kommunikationsteknologi; computers; datorer; households; hushåll; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Information society; Informationssamhället; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap